Cognitive Function Outcomes of Post-operative Mild to Moderate Traumatic Brain Injury using Combination of Mini-mental State Examination, Digit Span, and Constructional Praxis - Adam, Achmad; Ariono, Christian; Arifin, Muhammad Z.; Faried, Ahmad (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Progress has been made in developing systems of care that strives to minimize traumatic brain injury (TBI)-related morbidity and mortality. As the TBI survivors, one’s might be experienced cognitive function disorders that affect their quality of life. AIM: We sought to investigate the changes of cognitive function in patients with mild or moderate TBI. METHODS: This was a prospective study on 80 patients with mild and moderate TBI who had undergone surgery; 79 patients included in the study and one patient excluded due to incompletion of cognitive tasks. We assessed the cognitive function using a combination of mini-mental state examination (MMSE), digit span (DS), and constructional praxis (CP) tests. The correlations between clinical variables and neuropsychological tests were analyzed. RESULTS: In this study, majority of the patients were male (77.2%) with the mean of age 28.4 years, ranging from 15 to 74 years, predominantly was a young adult (15–20 years, 32.9%). In this series, majority of the patients had moderate TBI (69.6%). Most of the patients (55.7%) had 12 or more education years. MMSE examination revealed that 6.3% and 2.5% of patients had mild- and moderate-cognitive disturbances, respectively, significantly correlated with age (p = 0.049) and educational level (p = 0.008). From DS tests, 13.9% patients had attention disorders and significantly correlated with age (p = 0.015), educational level (p = 0.000), and the severity of TBI (p = 0.018). From CP tests, 24.1% and 5.1% had mild- and moderate-disturbances, respectively, significantly correlated with the severity of TBI (p = 0.025) and the type of intracranial lesion (p = 0.009). CONCLUSIONS: We found (using a combination of MMP, DS, and CP test) cognitive impairment more frequently in patients with moderate TBI, older age, and low education level, hence, emphasized the importance of holistic neuropsychological assessments and neurological rehabilitation for adequate management of patients with TBI.